Gastrointestinal disorders in autism spectrum disorder: an integrative review (Research, Society and Development, 2021)
Autistic Spectrum Disorder (ASD) is a syndrome that affects children in infancy and cannot be cured. In individuals with ASD, gastrointestinal disorders can aggravate behavioral issues, especially due to communication difficulties, which can impair learning and socialization. The present work is justified by the increased incidence of eating disorders in people with ASD, it is necessary to understand how certain dietary choices are contributing to their development and what other factors may be related. Thus, it is intended to understand the relationship between eating disorders and autism. An integrative review of eating disorders in children with ASD was carried out, 15 articles were selected for analysis using the years 2010 to 2021. It was observed that gluten and casein can have an important impact on the lives of patients with ASD, since they may be associated with damage to intestinal microvilli, contributing to poor absorption of these substances and gastrointestinal discomfort. It is concluded that it is of great importance for children with ASD to introduce a dietary intervention to improve physical and mental health, a balanced diet has a favorable impact on the mental health and well-being of these individuals.